Genetic and antigenic diversity of Theileria parva in cattle in Eastern and Southern zones of Tanzania: A study to support control of East Coast fever - Elisa, M.; Hasan, S.D.; Moses, N.; Elpidius, R.; Skilton, Robert A.; Gwakisa, P.S. (Cambridge University Press, 2015)
This study investigated the genetic and antigenic diversity of Theileria parva in cattle from the Eastern and Southern zones of Tanzania. Thirty-nine (62%) positive samples were genotyped using 14 mini- and microsatellite markers with coverage of all four T. parva chromosomes. Wright's F index (F ST = 0 × 094) indicated a high level of panmixis. Linkage equilibrium was observed in the two zones studied, suggesting existence of a panmyctic population. In addition, sequence analysis of CD8+ T-cell target antigen genes Tp1 revealed a single protein sequence in all samples analysed, which is also present in the T. parva Muguga strain, which is a component of the FAO1 vaccine. All Tp2 epitope sequences were identical to those in the T. parva Muguga strain, except for one variant of a Tp2 epitope, which is found in T. parva Kiambu 5 strain, also a component the FAO1 vaccine. Neighbour joining tree of the nucleotide sequences of Tp2 showed clustering according to geographical origin. Our results show low genetic and antigenic diversity of T. parva within the populations analysed. This has very important implications for the development of sustainable control measures for T. parva in Eastern and Southern zones of Tanzania, where East Coast fever is endemic.